2022
DOI: 10.1177/03611981211066899
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Daily Travel by Distances on the Spread of COVID-19: An Artificial Neural Network Model

Abstract: The continued spread of COVID-19 poses significant threats to the safety of the community. Since it is still uncertain when the pandemic will end, it is vital to understand the factors contributing to new cases of COVID-19, especially from the transportation perspective. This paper examines the effect of the United States residents’ daily trips by distances on the spread of COVID-19 in the community. The artificial neural network method is used to construct and test the predictive model using data collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
1
0
0
1
Order By: Relevance
“…This study highlighted an early-stage closed loop of transport behavior amid COVID-19, wherein more trips correlated with accelerated virus spread, resulting in higher risk perception and reduced trips, thereby perpetuating the loop. This nding is supported by another study by Truong and Truong (2022a), which found a positive relationship between daily trips and the number of COVID-19 cases. However, with the availability of vaccines in early 2021, this loop was broken, resulting in new transport patterns that showed an increase in travel in mid-2021.…”
Section: Previous Studiessupporting
confidence: 72%
“…This study highlighted an early-stage closed loop of transport behavior amid COVID-19, wherein more trips correlated with accelerated virus spread, resulting in higher risk perception and reduced trips, thereby perpetuating the loop. This nding is supported by another study by Truong and Truong (2022a), which found a positive relationship between daily trips and the number of COVID-19 cases. However, with the availability of vaccines in early 2021, this loop was broken, resulting in new transport patterns that showed an increase in travel in mid-2021.…”
Section: Previous Studiessupporting
confidence: 72%
“…Pandemi COVID-19 sudah menyerang Indonesia sejak Maret 2020. COVID-19 berawal mula dari Kota Wuhan di Provinsi Hubei, Cina terlebih dahulu (Troung, 2021). Selanjutnya, COVID-19 tersebar di berbagai wilayah pada tahun 2020 secara cepat.…”
Section: Pendahuluanunclassified